Front Cover: Prussian Blue‐Derived Synthesis of Hollow Porous Iron Pyrite Nanoparticles as Platinum‐Free Counter Electrodes for Highly Efficient Dye‐Sensitized Solar Cells (Chem. Eur. J. 54/2017). Issue 54 (9th August 2017) - Chen, Jeffrey E.; Fan, Miao‐Syuan; Chen, Yen‐Lin; Deng, Yu‐Heng; Kim, Jung Ho; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Ho, Kuo‐Chuan; Wu, Kevin C.‐W.
Abstract : Hollow porous iron pyrite nanoparticles that are deposited on the conducting substrate as the counter electrode (CE) in a dye‐sensitized solar cell (DSSC) are depicted. These nanoparticles offer a high surface area for the reduction of the triiodide ions. The DSSC directly converts the sunlight into electricity, which could power the flashlight without pollution. It is expected that the DSSC will emerge as a new class of low‐cost energy conversion device. More information can be found in the Communication by K.‐C. Ho, K. C.‐W. Wu et al. onpage 13284 .